Sengketa Pajak Dalam Ekonomi Digital: Anatomi Persoalan, Kekosongan Regulasi, dan Jalan Tengah yang Belum Ditemukan - Rhenata Sabrina; Mega Dewi Ambarwati (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid expansion of the digital economy has created significant challenges for tax systems, particularly in applying conventional tax rules to cross-border digital transactions. Since 2020, Indonesia has experienced a substantial increase in tax disputes involving digital transactions, reflected in both the number of cases brought before the Tax Court and the monetary value of disputed tax assessments. This study aims to analyze the distinctive characteristics of digital tax disputes, identify regulatory gaps and inconsistencies that contribute to such disputes, and evaluate the effectiveness of Indonesia's existing tax dispute resolution mechanisms. The research employs a normative juridical approach, utilizing doctrinal analysis of Indonesian Tax Court decisions issued between 2020 and 2024, complemented by a comparative study of digital taxation regulations in the European Union, India, and Singapore. The findings reveal that digital tax disputes in Indonesia are primarily concentrated in three areas: the determination of virtual permanent establishments, differing interpretations regarding Value Added Tax (VAT) on cross-border digital services, and regulatory uncertainty surrounding the taxation of cryptocurrency transactions. Furthermore, the study demonstrates that most disputes arise not from taxpayers' deliberate attempts to evade taxation, but rather from ambiguities and inconsistencies within the existing legal framework. These findings highlight the need for comprehensive regulatory reform and a more adaptive tax dispute resolution system capable of providing greater legal certainty, fairness, and effectiveness in addressing the complexities of the digital economy.